(In-)stability of singular equivariant solutions to the Landau–Lifshitz–Gilbert equation. (9th August 2013) - VAN DEN BERG, JAN BOUWE; WILLIAMS, J. F.
Abstract : In this paper, we use formal asymptotic arguments to understand the stability properties of equivariant solutions to the Landau–Lifshitz–Gilbert model for ferromagnets. We also analyse both the harmonic map heatflow and Schrödinger map flow limit cases. All asymptotic results are verified by detailed numerical experiments, as well as a robust topological argument. The key result of this paper is that blowup solutions to these problems are co-dimension one and hence both unstable and non-generic.